Efeitos do tratamento com a associação naltrexona/bupropiona em fígados de ratos obesos: aspectos histomorfométricos - Fernandes, Renan da Cunha (2019)
The objective of this study was to evaluate the action of Bupropion / Naltrexone association on weight, biochemical and histomorphometric aspects in obese wistar rats. Wistar rats were divided into two groups according to the diet offered: n = 10 normonutride (standard vivarium diet) and n = 10 obese (obesity-inducing diet) and then subdivided into 4 groups, where n = 5 normonutrients. no treatment, n = 5 normonutrients treated with NAL / BUP combination, n = 5 obese without treatment and n = 5 obese treated with NAL / BUP combination. The following were analyzed: body weight; Food consumption; Lee index; BMI; Biochemical and hematological profile, Morphometric and histological analysis of the livers of experimental animals after the treatment period with the Bupropion / Naltrexone combination. The combined use of NAL (1mg / kg) BUP (20mg / kg) promoted in obese animals a reduction in food intake measurements (5.74 ± 0.36 vs. 4.25 ± 0.23); body weight (461.5 ± 38.1 vs. 418.4 ± 43.7), Lee Lee indices (344.4 ± 13.7 vs. 321.7 ± 12.2) and BMI (0 , 91 ± 0.07 vs. 0.77 ± 0.08), weight reduction (5.22 ± 1.96 vs. 4.15 ± 0.120), increasing the volume of the hepatic middle lobe (13.01 ± 0.755). 14.00 ± 0.508), reducing the volume density of the hepatic middle lobe hepatocyte nucleus (0.65 ± 0.030 vs. 0.50 ± 0.025) and consequently leading to a reduction in the number of hepatocyte nuclei in the liver. hepatic middle lobe (71.4 ± 3.17 vs. 54.6 ± 2.69). increasing biochemical indices of alkaline phosphatase, AST and platelets. In addition to these results, a reduction in hepatic steatosis pattern was observed in obese animals through histological analysis. These results indicate that the combined use of NAL / BUP promotes a reduction in the consumption of densely energetic foods, which contributes to weight loss. improved glycemia, reduced hepatic steatosis rates and decreased morphometric changes in liver tissue.